Financial performance of Malaysian companies listed in top 2016 Forbes Global 2000 / Ammar Faiz Zainol - Zainol, Ammar Faiz (2017)
The purpose of this paper is to examine the impact of financial ratios on the financial performance of Malaysian companies listed in top 2016 Forbes Global 2000. These companies are those who still maintained their position among best 2000's companies around the world. This paper would like to analyze their performance throughout any financial crisis faced by many sectors. A panel data has been used and secondary data has been analyzed to estimating the relationship between financial ratios and firm's financial performance. This paper will use company's net income as the dependent variable. While liquidity ratio, leverage ratio, profitability ration, marketable ratio, and activity ratio act as independent variables. Curent ratio (CR) represent the liquidity ratio, debt ratio (DR) represent the leverage ratio, net profit margin (NPM) represent the profitability ratio, total asset turnover (TATO) represent the activity ratio, and earning per share (EPS) represent the marketable ratio. The data was collected from 4 Malaysian companies listed in top 2016 Forbes Global 2000 as their industries representative. All information involved was derived from company's website, online journal, and Thompson Datastream . This paper will run all the data collected from 2000-2016 (17 years, 68 observations). In addition, econometric test are employed to supervise the relationship of the variables involved. Data collecting and analyzing have been worked out by using the intelligent data software called E-views. Moreover, the findings of the impact of the financial ratio which are CR, TATO, DR, NPM and EPS have a positive relationship on the company's performance.